Kepemimpinan Kepala Sekolah dan Peningkatan Kualitas Belajar di Sekolah (Studi Kasus SDN 5 Terara Lombok Timur) - Nurlaili, Nurlaili; Bafadal, Robyan Endruw (Universitas Hamzanwadi, 2018)
Leadership is most important for organization, including school organizatioin. Leader is more influential for the stakeholder of elementary education. This article describe what was school leader do to improving his school. With used manajemen process (planning, organizing, acting, and controlling) learning process was better. Government aid is important, but leadership is more important for that. Keywords: Leadership, Learning Process